Terminological metaphor and multimodality - Pissolato de Oliveira, Luciana (Lenguas Modernas, 2018)
Specialized texts within their different specialization levels constitute ‘conceptualization offers’ about a certain scientific discipline. Traditionally, the role of creator of this specialized cognitive system was attributed to the terminologicalset and its surroundings (the characteristics of scientific discourse). However, the linguistic element cannot be responsible, on its own, for the construction of knowledge in its wider sense: considering the text in its whole – which implies knowing the characteristics of the scientific genre, its ways of expression and materialization –, is critical for the more detailed analysis of a discourse, whatever is the situation context. In this article we aim to demonstrate that the specialized text must be considered a multimodal space, in which images (such as figures and tables) play a critical role, not only in the conceptualization or in the construction of knowledge, but they promote the evolution of specialized knowledge. As an illustration, we will analyse the role of visual metaphors in texts with different levels of specialization and its implication in the construction of sense in the scientific discourse.